Pelatihan Olah Data Riset Akuntansi Berbasis Data Panel Dengan Software Stata Pada Model Penelitian Intervening dan Moderating di PDIE Konsentrasi Akuntansi Universitas Trisakti - Tambun, Sihar; Sitorus, Riris Rotua (Jurnal Pemberdayaan Nusantara, 2025)
Stata is a powerful software for statistical data processing, including panel data processing data originating from financial and accounting data. Researchers in the Doctoral Program in Economics, Accounting Concentration, Trisakti University, have not been able to use this software. The training was held as a community service program from lecturers at the Universitas 17 Augustus 1945 Jakarta and lecturers from Universitas Esa Unggul. The purpose of the training was to educate researchers in the Doctoral Program in Economics, Accounting Concentration at Trisakti University, on how to process accounting research data using panel data by utilizing Stata software. The training includes how to input data, how to test data according to research needs, and how to interpret the results of data processing. The output of this training is that participants are able to independently process panel data using Stata software, and are able to interpret the results of accounting research from a statistical perspective. The results of the evaluation of the success of the training were 12% of participants very understanding, 81% of participants understood and the remaining 7% of participants did not understand. Although the majority of participants understood and understood very well, participants need to train this skill continuously so that they become more accustomed and can independently process accounting research data based on this panel data.